IMPACT OF ORGANIC WEED MANAGEMENT PRACTICES ON WEEDS CONTROL, GROWTH AND YIELD OF MAIZE (Zea mays L.) - R. Chethan; Ch. Bharghava Rami Reddy (The Journal of Research ANGRAU, 2024)
This field experiment on organic weed managament practices was conducted during rabi, 2021-22 at wetland farm of S.V. Agricultural College, Tirupati, with 10 management practices in a randomized block design and replicated thrice. Among all the organic weed management practices, lower weed density and dry weight with higher weed control efficiency and weed control index was recorded with corn gluten meal 3.5 t ha-1 as pre-emergence (PE) followed by hand weeding (HW) at 30 days after sowing (DAS), however, it was statistically comparable with HW twice at 15 DAS and 30 DAS. Significantly higher growth parameters, yield attributes and kernel and stover yield of maize were recorded with corn gluten meal 3.5 t ha-1 as pre-emergence followed by HW at 30 DAS over rest of the treatments. The next best treatment in reducing density and dry weight of weedswith higher growth parameters, yield attributes and yield was HW twice at 15 DAS and 30 DAS, which was however, at par with groundnut shells mulch 12.5 t ha-1 and mango leaves mulch 5 t ha-1.